Japan’s “Top Global University” Project - Shimmi, Yukiko; Yonezawa, Akiyoshi (International Higher Education, 2015)
Thirty-seven Japanese universities were selected as Japan’s “Top Global University” project, a governmental funding initiative in September, 2014. This project aims at promoting universities’ international recognition and competitiveness by internationalizing and conducting university reforms on various aspects of the university operation. After describing the characteristics of the current project, we discuss the potential consequences, such as, micromanagement of the government on the university reform, isomorphic standardization of the internationalization approach, and the widening gap among universities.